Identification of a Novel Strong and Ubiquitous Promoter/Enhancer in the Silkworm Bombyx mori - Tsubota, Takuya (G3 (Bethesda), 2014)
Transgenic techniques offer a valuable tool for determining gene functions. Although various promoters are available for use in gene overexpression, gene knockdown, and identification of transgenic individuals, there is nevertheless a lack of versatile promoters for such studies, and this dearth acts as a bottleneck, especially with regard to nonmodel organisms. Here, we succeeded in identifying a novel strong and ubiquitous promoter/enhancer in the silkworm. We identified a unique silkworm strain whose reporter gene showed strong and ubiquitous expression during the establishment of enhancer trap strains. In this strain, the transposon was inserted into the 5′UTR of hsp90, a housekeeping gene that is abundantly expressed in a range of tissues. To determine whether the promoter/enhancer of hsp90 could be used to induce strong gene expression, a 2.9-kb upstream genomic fragment of hsp90 was isolated (hsp90(P2.9k)), and its transcriptional activation activity was examined. Strikingly, hsp90(P2.9k) induced strong gene expression in silkworm cell cultures and also strongly induced gene expression in various tissues and developmental stages of the silkworm. hsp90(P2.9k) also exhibited significant promoter/enhancer activity in Sf9, a cell culture from the armyworm, suggesting that this fragment might possibly be used as a gene expression tool in other Lepidoptera. We further found that 2.0 kb of hsp90(P2.9k) is sufficient for the induction of strong gene expression. We believe that this element will be of value for a range of studies such as targeted gene overexpression, gene knockdown and marker gene expression, not only in the silkworm but also in other insect species.